SAT0661 MXA IS A CLINICALLY APPLICABLE BIOMARKER FOR TYPE I INTERFERON ACTIVATION IN SYSTEMIC LUPUS ERYTHEMATOSUS AND SYSTEMIC SCLEROSIS. (June 2019) - Huijser, Erika; van Helden-Meeuwsen, C.G.; Groot, Noortje; Bodewes, Iris LA; Javad Wahadat, M.; Schreurs, Marco Wj; Daele, Paul LA van; Dalm, Virgil Ash; Laar, Jan van; Martin van Hagen, P; Waris, Matti; Kamphuis, Sylvia; et al.
Abstract : Background: Activation of the type I interferon (IFN) system has been found in large subsets of patients with systemic autoimmune diseases. This is usually assessed with a laborious quantification of IFN-stimulated genes. An easier and cheap biomarker would facilitate implementation of type I IFN measurements in diagnostic laboratories. Previously, we described Myxovirus resistance protein 1 enzyme immunoassay (MxA-EIA) for systemic evaluation of type I IFN activity in primary Sjögren's syndrome [1]. Objectives: To assess the applicability of the MxA-EIA to detect systemic type I IFN activation in patients with systemic lupus erythematosus (SLE) and systemic sclerosis (SSc). Methods: Whole blood intracellular MxA protein levels were measured in SLE (discovery cohort: n=25; replication cohort retrieved from the CHILL-NL study [2]: n=102), SSc (n=28) and healthy controls (HC) using the MxA-EIA. IFN scores were determined from whole blood gene expression of interferon-stimulated genes IFI44, IFI44L, IFIT1, IFIT3, and MxA by RT-PCR. Results: MxA levels were significantly elevated in patients with SLE and SSc compared to HC and highly correlated to IFN scores (rs =0.735 to rs =0.854, p≤0.003). MxA-EIA robustly discriminated (AUC=0.938 to AUC=0.991, p≤0.007) between low and high type I IFN activity in SLE and SSc patients with a specificity of 100% and a sensitivity of 87.5 to 94.7%. Patients with autoantibodies against SM, RNP, SSA/Ro, or SSB/La antigens showed higher MxA levels and IFN scores compared to patients without these antibodies. Conclusion: Intracellular MxA is an easy applicable and clinically relevant biomarker for systemic type I IFN bioactivity in SLE and SSc. MxA-EIA could be used to identify patients eligible for IFN-targeting treatments and potentially to monitor treatment responses. References: [1] Maria NI, Brkic Z, Waris M, van Helden-Meeuwsen CG, Heezen K, van de Merwe JP, van Daele PL, Dalm VA, Drexhage HA, Versnel MA. MxA as a clinically applicable biomarker for identifying systemic interferon type I in primary Sjogren's syndrome. Ann Rheum Dis 2014;73:1052-9. [2] Groot N, Shaikhani D, Teng YKO, de Leeuw K, Bijl M, Dolhain R, Zirkzee E, Fritsch-Stork R, Bultink IEM, Kamphuis S. Long-term clinical outcomes in a cohort of adults with childhood-onset Systemic Lupus Erythematosus. Arthritis Rheumatol 2018; doi: 10.1002/art.40697. Acknowledgement: The research for this manuscript was (partly) performed within the framework of the Academic Centers for Rare Immunological Diseases and Inflammunity, and the Erasmus Postgraduate School Molecular Medicine. Disclosure of Interests: Erika Huijser: None declared, C.G. van Helden-Meeuwsen: None declared, Noortje Groot: None declared, Iris LA Bodewes: None declared, M. Javad Wahadat: None declared, Marco WJ Schreurs: None declared, Paul LA van Daele: None declared, Virgil ASH Dalm: None declared, Jan van Laar: None declared, P Martin van Hagen: None declared, Matti Waris: None declared, Sylvia Kamphuis: None declared, Marjan Versnel Grant/research support from: MAV received financial support from Domainex.